The Effect of Urease Inhibitors Coated Urea on the Growth, Physiological Activities and Yield of Maize (Zea mays L.) in Inceptisol Jogonalan, Klaten - Fransisca Christiana Dewi; Eka Tarwaca Susila Putra; Cahyo Wulandari (Jurnal Ilmu Pertanian, 2018)
An approach to minimize the loss of nitrogen (N) evaporating from urea is by inhibiting urease activity by urea coating with N- (n-butyl) thiophosphoric triamide (NBPT) and N- (n-propyl) thiophosphoric triamide (NPPT). The effect of urease inhibitor to minimize N loss has not been done in inceptisol soil. The purpose of this study was to study the effect of urease inhibitor coated urea on growth, physiological activity and yield of maize in Inceptisol Jogonalan, Klaten, Indonesia. The treatment was laid out in a Randomized Complete Block Design with 4 replications namely N0 (without fertilizer), N1 (urea + NBPT 348 kg ha-1) and N2 (urea + NBPT 278 kg ha-1). All treated plants was fertilized once in one growing season 3 weeks after planting (WAP). Observations were done on several variables: soil physicochemical characteristics, plant physiological activity as well as growth and yield of maize. Data were analyzed using Analysis of Variance (ANOVA), and then the mean comparisons were done by using Least Significance Difference (LSD) test at 5%. The results showed that fertilization affected all observed variables. The effect of urea-coated urea inhibitor urease (NBPT+NPPT) compared with N0 (control) showed very optimum result, especially in N2 treatment. The urea coated with NBPT + NPPT (urease inhibitors) was more effective at lower dose of 278 kg ha-1 and tended to provide better results indicated by the growth and yield of maize in Inceptisol, Jogonalan, Klaten. The better growth as well as the higher yield of maize that was indicated by seed weight of 11,45 tons ha-1 and 100-seed weight of 37.75 g were obtained from N2 treatment as compared to other treatments. The hybrid maize (P35) has an optimum yield potential of 12.1 tons of dry pipes per hectare.